2022
DOI: 10.15302/j-fase-2022443
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Use and Management in Orchards and Vegetable Fields in China: Challenges and Solutions

Abstract: HIGHLIGHTS• Excessive application of N fertilizers in orchards and vegetable fields (OVFs) in China is particularly common. • Long-term excessive application of N fertilizers has made OVFs hotspots for N surplus and loss in China. • Nitrate accumulation in the soil profile is the main fate of N fertilizers in OVF systems. • Reducing the N surplus is the most effective way to reduce N loss and increase NUE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For instance, land used for growing vegetables, which often undergo multiple annual harvests, generally experiences higher irrigation and fertilizer application rates compared with cereal land. Consequently, these areas tend to accumulate more nitrogen in the vadose zone, thereby resulting in higher groundwater nitrate concentrations. ,,, Furthermore, it is important to consider potential point sources of nitrate pollution. Previous study has shown that point source pollution contributes significantly to the elevated nitrate concentration in the hill region of the NCP …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, land used for growing vegetables, which often undergo multiple annual harvests, generally experiences higher irrigation and fertilizer application rates compared with cereal land. Consequently, these areas tend to accumulate more nitrogen in the vadose zone, thereby resulting in higher groundwater nitrate concentrations. ,,, Furthermore, it is important to consider potential point sources of nitrate pollution. Previous study has shown that point source pollution contributes significantly to the elevated nitrate concentration in the hill region of the NCP …”
Section: Results and Discussionmentioning
confidence: 99%
“…Consequently, these areas tend to accumulate more nitrogen in the vadose zone, thereby resulting in higher groundwater nitrate concentrations. 23,26,69,70 Furthermore, it is important to consider potential point sources of nitrate pollution. Previous study has shown that point source pollution contributes significantly to the elevated nitrate concentration in the hill region of the NCP.…”
Section: Key Features Impacting Lag Time-considered Nitrate Groundwat...mentioning
confidence: 99%
“…To some extent, it reflects the nitrogen use efficiency [58]. Therefore, clarifying the N surplus in an agricultural system is critical for controlling N losses [59]. It has been shown that a positive correlation does exist between nitrogen surplus and soil alkaline nitrogen content [60], indicating that the higher the alkaline nitrogen content, the higher the soil nitrogen surplus, along with a correspondingly increased potential risk of surface source pollution.…”
Section: Nitrogen Fertilizer Rate and N Surplusmentioning
confidence: 99%